PERILAKU TIANG BOR PENOPANG INFRASTRUKTUR PADA TANAH LUNAK AKIBAT BEBAN STATIK - Aspar, Wimpie Agoeng N. (Badan Pengkajian dan Penerapan Teknologi, 2010)
Bored piles have been used to support transportation infrastructures (offices, a terminal building, power house, warehouses and workshop) in a harbor. The bored piles were penetrated into mostly old alluvial deposits and dilluvial deposits of very stiff marine clay with traces of shell debris. A bored pile was tested as part of this research program to verify the accuracy of the predicted pile capacities. The proposed static prediction capacity methods include Meyerhof, a, b and l methods. The results of the analysis show that Meyerhof method (1951) with inputs of laboratory test data provides closely agreement with static loading test results. The other methods give somewhat conservative prediction. This paper discusses bearing capacity analysis of bored piles based on soil characteristics and static loading test results. Results of the analysis indicate that the bored piles capable of resisting load transmitted from the upper structure. The research will be of interest to many practicing engineers using this kind of piles.